2014
DOI: 10.1155/2014/217142
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Biodistribution of Zinc-Enriched Yeast in Rats

Abstract: Zinc-enriched yeast (ZnY) and zinc sulfate (ZnSO4) are considered zinc (Zn) supplements currently available. The purpose of the investigation was to compare and evaluate pharmacokinetics and biodistribution of ZnY and ZnSO4 in rats. ZnY or ZnSO4 were orally administered to rats at a single dose of 4 mg Zn/kg and Zn levels in plasma and various tissues were determined using inductively coupled plasma-optical emission spectrometry. Maximum plasma concentration values were 3.87 and 2.81 μg/mL for ZnY and ZnSO4, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The time-concentration profiles of both complexes are in agreement with the findings of a previous study [ 32 ]. The differences in the profiles of Zn II complexes 1 and 2 observed in this study are probably due to their structural differences regarding the composition of their ligands.…”
Section: Resultssupporting
confidence: 91%
“…The time-concentration profiles of both complexes are in agreement with the findings of a previous study [ 32 ]. The differences in the profiles of Zn II complexes 1 and 2 observed in this study are probably due to their structural differences regarding the composition of their ligands.…”
Section: Resultssupporting
confidence: 91%
“…[12] The increased bioavailability of the trace elements using yeast or bacteria as a vehicle compared with the inorganic forms of the trace element have been reported in many studies. [11,[14][15][16] The use of microorganisms for delivering of these nutrients is of relevance for the production of functional foods with these micronutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Ortman and Pehrson [8] reported that organic Se from Se-enriched yeast is an ideal supplement because animals retain and absorb it more efficient than the inorganic form of Se. Zn-enriched yeast is naturally integrated by the growing yeast into its own structure to improve the bioavailability of Zn and reduce the sides effects of Zn [9] . In mammals, chromium (Cr) has been recognized to be a biologically essential trace element.…”
Section: Introductionmentioning
confidence: 99%